2016
DOI: 10.1186/s12896-016-0299-0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of AtOxR gene improves abiotic stresses tolerance and vitamin C content in Arabidopsis thaliana

Abstract: BackgroundAbiotic stresses are serious threats to plant growth, productivity and result in crop loss worldwide, reducing average yields of most major crops. Although abiotic stresses might elicit different plant responses, most induce the accumulation of reactive oxygen species (ROS) in plant cells leads to oxidative damage. L-ascorbic acid (AsA, vitamin C) is known as an antioxidant and H2O2-scavenger that defends plants against abiotic stresses. In addition, vitamin C is also an important component of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In plants, l ‐ascorbic acid (AsA; vitamin C) is a major antioxidant with roles in photosynthesis, respiration, cell division, growth regulation, integrating phytohormone signalling and ageing (Sanmartin et al ., 2003; Barth et al ., 2006; Kotchoni et al ., 2009; Smirnoff, 2011; Hanxia et al ., 2015; Bu et al ., 2016; Y. Yu et al ., 2019; Zhang et al ., 2020; Bulley et al ., 2021). As an essential micronutrient that humans have lost the ability to produce, AsA is required for key metabolic functions in humans and must be obtained from the diet, mainly from fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…In plants, l ‐ascorbic acid (AsA; vitamin C) is a major antioxidant with roles in photosynthesis, respiration, cell division, growth regulation, integrating phytohormone signalling and ageing (Sanmartin et al ., 2003; Barth et al ., 2006; Kotchoni et al ., 2009; Smirnoff, 2011; Hanxia et al ., 2015; Bu et al ., 2016; Y. Yu et al ., 2019; Zhang et al ., 2020; Bulley et al ., 2021). As an essential micronutrient that humans have lost the ability to produce, AsA is required for key metabolic functions in humans and must be obtained from the diet, mainly from fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, higher levels of AtOXR, which encodes transmembrane OXR protein, was observed in SF-primed plants ( Table 1). Overexpression of AtOXR in Arabidopsis results in ascorbate accumulation, concomitant with an increased tolerance to oxidative stress [63]. Notably, expression of 1-myo-inositol-1-phosphate synthase encoding MIPS1 was elevated in SF-primed plants.…”
Section: Detoxification Of Pq-induced Rosmentioning
confidence: 99%
“…In addition, we also found that the homologous gene AT5G57345 in Arabidopsis , a single copy gene, is localized to ER and expressed in the whole plant and induced expression in response to abiotic stress. Although the function of AT5G57345 is unclear, overexpression can lead to increased tolerance to abiotic stress and increased ascorbic acid content ( Bu et al, 2016 ). In addition, we also found that the expression level of LOC_Os06g47970 in S125 was much higher than that in S87.…”
Section: Discussionmentioning
confidence: 99%